EVALUATION OF QUALITY OF LIFE OF PATIENTS WITH MALIGNANCY DURING THE COVID-19 PANDEMIC - ASGHAR, RS; JAVAID, U; BAIG, MAA; RAFIQUE, F; FATIMA, K; AFZAL, MB (Biological and Clinical Sciences Research Journal, 2022)
The study's objective was to evaluate patients' quality of life with malignancy during the Covid-19 pandemic. This study was conducted at the Department of Oncology, Anmol Hospital, Lahore, from August 2020- February 2021. 250 stage III and IV cancer patients undergoing chemotherapy were selected for the study. The patients were asked to complete a questionnaire regarding the ongoing covid-19 pandemic, their cognitive responses to it, their preventive measures, and access to medical treatment. In addition, patients were also asked to respond to the European Organization for Research and Treatment of Cancer quality of life. The data analysis showed a significantly low quality of life for pandemic cancer patients (42.6) compared to non-pandemic patients (61.5). The physical (69.1 vs. 71.2) and emotional functioning (69.5 vs. 71.5) did not vary significantly in both groups; however, the cognitive (70.8 vs. 83.2) and social functioning (68.3 vs. 75.1) were significantly high in the reference group (p<0.001). The pandemic did not have much effect on the role functioning of cancer patients. The symptom scale showed a higher value in pandemic patients than the non-pandemic patients, with insomnia (41.0), fatigue (42.7), and appetite loss (27.4) being the most common symptoms. Thus, it can be concluded that the quality of life of cancer patients is seriously affected by covid-19. Thus, necessary measures should be taken to improve such circumstances.